ANFIS-PSO analysis on axisymmetric tetra hybrid nanofluid flow of Cu-CNT-Graphene-Tio2 with WEG-Blood under linear thermal radiation and inclined magnetic field: A bio-medicine application - Maddina Dinesh kumar; José Luis Díaz Palencia; G. Dharmaiah; A. Wakif; S. Noeiaghdam; U. Fernandez-Gamiz; S. Dinarvand (Heliyon)
Background: The development of heat transfer devices used for heat conversion and recovery in several industrial and residential applications has long focused on improving heat transfer between two parallel plates. Numerous articles have examined the relevance of enhancing thermal performance for the system's performance and economics. Heat transport is improved by increasing the Reynolds number as the turbulent effects grow. Applications: Regarding heat transfer, hybrid nanofluids are superior to mono nanofluids. The hybrid fluid of Cu-CNT + Graphene + TiO2/WEG-Blood, which is subject to heat transfer in a channel between two parallel plates with an angled magnetic field and linear thermal radiation, has numerous applications in engineering, industry, and biomedical research, such as electronic cooling, drug delivery, cancer treatment, optics, missiles, satellites, transformer-electronic cooling, and military solar-equipment. Objective: Examining the qualities of mass, flow, and heat transmission is the aim of the study of a hybrid Cu-CNT- Graphene-TiO2/WEG-Blood nanofluid as it moves via a tube of porous material that is exposed to linear thermal radiation, inclined magnetic, Forchheimer, and buoyancy influences. ANFIS-PSO model is assumed. Method: Applying the ODE45 integration technique to the given numerical solutions yields non-linear, non-dimensionalized, and highly partial differential equations that control the momentum, energy, and concentration. Consequently, the numerical simulation shows the concentration, velocity, and temperature profiles of the hybrid Cu-CNT- Graphene-TiO2/WEG-Blood nanofluid. A strong concordance is noted between recent and past results. Significance and primary outcomes: Radiation regulates the microchannel temperature distribution, which significantly contributes to cooling the flow transport system, and the thermal radiation parameter shows that radiation has a retarding influence on the temperature profile.